Results of Implementing a Career Guidance Technology for Developing Students’ Career Orientation in the Context of Specialized Education - Morin, Oleh (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The article addresses the issue of implementing a career guidance technology for developing students’ career orientation within the context of specialized education – a highly relevant matter amid the transformation of the modern Ukrainian educational system. The shift in the school education paradigm, the transition to the New Ukrainian School, and the focus on personal development and selfrealization of each student underscore the urgent need for effective career guidance technologies that can provide students with the opportunity for conscious, motivated, and socially meaningful educational and professional choices. The essence of the proposed career guidance technology lies in its comprehensive impact on all components of the student's personality as a subject of career self-determination: motivational, cognitive, reflective, and volitional. The technology is based on person-centered, reflexive, axiological, and activitybased approaches, drawing on I. Bekh’s concept of spiritual and moral development. The goal is not only to provide students with knowledge about professions but also to develop their internal readiness to choose a life and professional path, to understand the social significance of labour, and to cultivate the ability to make responsible decisions. Methodologically, the study is grounded in a combination of theoretical and empirical methods, including the analysis of scholarly sources, pedagogical modelling, formative experiments, and diagnostics of students' career orientation levels. During the study, a five-component model of the technology was tested (target, procedural-practical, control and evaluation, managerial, and resultative components) and implemented in specialized schooling. The results demonstrated a significant increase in students’ awareness of career choice and motivation for career development, and a decrease in the proportion of students with a low level of orientation. Specifically, the high level increased by 12 % in the experimental group, while the low level decreased by 27 %, indicating the effectiveness of the proposed technology. The scientific novelty of the research lies in the development and implementation of a systemic career guidance technology integrated into specialized education, which provides not only informational but also value-based and motivational support for students' career self-determination. For the first time, the key principles of pedagogical adaptation of such a technology to the conditions of senior specialized school have been outlined, taking into account the factors of flexibility, variability, continuity, and differentiation (furcation). The scope of application of the developed technology includes general secondary education institutions implementing specialized education and may be helpful to teachers, school psychologists, class teachers, social pedagogues, and school administrators in developing systems of career support. The technology has the potential to scale, taking into account digital tools, regional context, and individual educational needs. It may also serve as a foundation for further developments in student career counselling.